From expectation to experience : graduates entering a large corporation - Nicholson, Nigel [Verfasser]; Arnold, John [Verfasser] (My University, 1991)
"The paper reports a longitudinal study of new and recently recruited graduates to an oil company, to evaluate how initial expectations compared with experience, and how needs, interests and work activities changed over time post-entry. Results showed that new entrants had unrealistic expections, especially of having more managerial job content than they were assigned initially, but this increased with subsequent experience to reach expected levels. Socialization effects were evident, especially ba job function, but not by gender. the work orientations and job experiences of commercial and technical graduates developed on divergent paths over time, suggesting more positive personal growth over their early careers for the commercial graduates." (author's abstract) ((en)) Der Beitrag befasst sich mit den Erwartungen und Erfahrungen, die Hochschulabsolventen bei ihrem beruflichen Einstieg in ein britisches Ölunternehmen machten. (IAB)
Keywords: P 2.1.5 Fachhochschul- und Hochschulreife; G 2.3.1 Arbeitsteilung & -organisation; S 3.2 Unternehmen und Behörden; G 1.3.3 Bildungs- & Erwerbsbiografien; G 2.3.2 Arbeits- & Beschäftigungsverhältnisse; G 2.3.3 Arbeitsformen, Techniken; G 2.4.1 Bildungs- und Berufswege; G 2.4.4 Biografiegestaltung; Hochschulabsolvent; Berufliche Sozialisation; Betrieb; Berufsverlauf; Arbeitsanforderungen; Unterforderung; Beruflicher Aufstieg; Geschlechtsspezifische Faktoren; Quantitative Angaben